Role of Chromogranin A in the Diagnosis and Follow-up of Neuroendocrine Tumors: Real-World Experience. Issue 8 (September 2022) - Nguyen, Mike; Li, Michelle; Travers, Avraham; Segelov, Eva
Abstract : Objective: The aim of this study was to assess the utility of serum chromogranin A (CgA) along the clinical pathway of patients with neuroendocrine tumors (NETs). Methods: A retrospective review of medical records was conducted of patients with NET who had at least 1 measurement of CgA between January 2015 and April 2021 at a large metropolitan Australian hospital. Chromogranin A was classified as increased or decreased if there was at least a 25% change in sequential levels and was compared with disease response by anatomical or functional imaging if within 6 weeks (considered concurrent). Results: Of 102 patients with NETs, 67 had at least 1 serum CgA level: 50 had been ordered during diagnostic workup, of which 33 were elevated (sensitivity: 66%; 95% confidence interval, 51%–79%). Of 129 CgA results concurrent with imaging, the sensitivity for detecting progressive disease was 28% (95% confidence interval, 15%–44%). Conclusions: Our findings support previous concerns that CgA adds little value in clinical decision-making.